Digital twinning as an act of governance in the wind energy sector. Issue 127 (January 2022) - Solman, Helena; Kirkegaard, Julia Kirch; Smits, Mattijs; Van Vliet, Bas; Bush, Simon
Abstract: Digital twins have emerged as novel technology in the wind energy sector that enables the design, monitoring and prediction of wind turbine performance. Despite growing attention on their potential, little is known about how digital twins are designed, by whom and how their design choices affect multiple aspects of decision making in the development of wind energy. Using a framework of co-production, this paper examines digital twins as boundary objects and the role of twinning as boundary work that involves an active process of design and affects multiple aspects of decision making in the development of wind energy. Our results demonstrate how the design of digital twins evolves throughout the twinning process, affected by regulation, choices of expert twinners on data and models, and what constitutes a matter of concern. We shed light on the role of these twinners in influencing which actors and their matters of concern are included and excluded during the twinning process. Our understanding of twinning as an active process of governance by design more clearly reveals how digital twins are not objective representations of reality, but a function of boundary work. We conclude that more transparency is needed over how digital twins are designed to enhance their role as technologies that foster a transition towards more sustainable energy systems and decision-making over wind energy technologies and their integration in landscapes. Highlights: There is limited understanding of how digital twins are designed We focus on wind energy and 'twinning' as an act of governance We unpack twinning as boundary work and digital twins as boundary objects Twinning involves choices about data, models, concerns and regulation Priorities and focus in twinning may steer wind energy transitions